Oxidative insult can induce malaria-protective trait of sickle and fetal erythrocytes - Cyrklaff, Marek; Srismith, Sirikamol; Nyboer, Britta; Hoffmann, Angelika; Lasitschka, Felix; Müller, Ann-Kristin; Sanchez, Cecilia P.; Frischknecht, Friedrich; Lanzer, Michael (Nature Communications, 2016)
Carriers of haemoglobinopathies are protected from severe malaria, likely due to reduced surface expression of virulence factors. Here, Cyrklaff et al.